Carrier lifetimes in green emitting InGaN/GaN disks‐in‐nanowire and characteristics of green light emitting diodes. Issue 5 (29th January 2013) - Jahangir, Shafat; Banerjee, Animesh; Bhattacharya, Pallab; Krishna, Sanjay; Plis, Elena
Abstract Improvement in the internal quantum efficiency (IQE) of InGaN/GaN disks‐in‐nanowires by surface passivation is demonstrated. The highest IQE achieved through surface passivation for green emitting (λ=540 nm) InGaN/GaN disks‐in‐nanowires is ∼53%. Radiative and nonradiative carrier lifetimes are calculated for as‐grown and surface passivated green emitting disks‐in‐nanowires. Passivated green sample exhibits a room temperature radiative lifetime of ∼748 ps, which is much smaller than that of equivalent quantum wells. Electroluminescence measurements on passivated green light emitting diodes containing InGaN disks demonstrate no roll over or efficiency droop up to 375 A/cm2, and exhibit a blue‐shift of 7 nm in peak wavelength. An enhancement in the light output due to surface passivation is observable in the relative external quantum efficiency of the surface passivated devices as compared with the as‐grown samples. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)